Development of Basic Communication Counseling Skills Video for PGSD Students of STKIP Muhammadiyah Manokwari - Siti Fatimahtun Zahra; Rahayu Pertiwi Sari (Program Studi bimbingan Konseling PPs UNM Makassar, 2020)
This study aims to determine; (1) A description of the PGSD student's needs of STKIP Muhammadiyah Manokwari towards mastering basic communication counseling skills consisting of attending, empathy, and minimal encouragement. (2) Video prototype of basic counseling communication skills, in the form of attending, empathy, and minimal encouragement skills. (3) The acceptance of video in the form of attending, empathy, and minimal encouragement skills. This research is research and development using the stages of the Borg & Gall research model. Data collection techniques used were interviews and scale. The results showed that; (1) The needs of PGSD STKIP Muhammadiyah Manokwari students for the development of video basic counseling communication skills such as attending skills, empathy, and minimal encouragement are very large. (2) The developed video prototype is valid and acceptable so that it can be used in instructional learning and counseling. (3) The acceptance of the video given to 10 students and 1 lecturer of BK courses in a small group test shows a very positive (high) response.